PENGARUH PARTNERSHIP TERHADAP KEUNGGULAN BERSAING PADA PT. SERVITAMA INTERNUSA - Ainul Fuadi; Iwan Nauli Daulay; Prima Andreas Siregar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The study aims to determine the effect of internal partnership and external partnership on competitive advantage at PT. Servitama Internusa. The population in this study covers all employees of PT. Servitama Internusa as well as consumers and suppliers who cooperate with the company. The type of data used in this study is the primary data sourced from the results of questionnaires and secondary data sourced from books, reports, and journals as instruments to prove the results of research, and to test the hypothesis in this study is to use multiple linear regression analysis with the help of the program SPSS. The result of research shows that: 1) there is positive and significant influence of internal partnership to competitive advantage. 2) there is a positive and significant influence of external partnership on competitive advantage. 3) Internal partnership and External partnership simultaneously have a significant positive effect on competitive advantage at PT. Servitama Internusa.Keywords : Internal partnership and External partnership and Competitive Advantage.